Pneumatic Quasi-Passive Actuation for Soft Assistive Lower Limbs Exoskeleton - Di Natali, Christian; Sadeghi, Ali; Mondini, Alessio; Bottenberg, Eliza; Hartigan, Bernard; De Eyto, Adam; O'Sullivan, Leonard; Rocon, Eduardo; Stadler, Konrad; Mazzolai, Barbara; Caldwell, Darwin G.; Ortiz, Jesús (Frontiers in Neurorobotics, 2020)
There is a growing international interest in developing soft wearable robotic devices to improve mobility and daily life autonomy as well as for rehabilitation purposes. Usability, comfort and acceptance of such devices will affect their uptakes in mainstream daily life. The XoSoft EU project developed a modular soft lower-limb exoskeleton to assist people with low mobility impairments. This paper presents the bio-inspired design of a soft, modular exoskeleton for lower limb assistance based on pneumatic quasi-passive actuation. The design of a modular reconfigurable prototype and its performance are presented. This actuation centres on an active mechanical element to modulate the assistance generated by a traditional passive component, in this case an elastic belt. This study assesses the feasibility of this type of assistive device by evaluating the energetic outcomes on a healthy subject during a walking task. Human-exoskeleton interaction in relation to task-based biological power assistance and kinematics variations of the gait are evaluated. The resultant assistance, in terms of overall power ratio (Λ) between the exoskeleton and the assisted joint, was 26:6% for hip actuation, 9:3% for the knee and 12:6% for the ankle. The released maximum power supplied on each articulation, was 113:6% for the hip, 93:2% for the knee, and 150:8% for the ankle.